Text mining of news articles to detect violation of human rights - Mahmud, A M Saif; Ahmed, Talha; Hakim, Azrin; Sultana, Tanjida (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.